The Influence Of Internal Audit and Internal Control On Fraud Prevention At Bank BJB Sharia Cirebon Branch - Febriyani, Aulia; Nakhwatunnisa, Haulah; Setiowati, Nur Eka (UIN Mataram, 2024)
Abstract This study aims to determine the effect of internal audit and internal control on fraud prevention at Bank BJB Syariah Cirebon Branch. This study uses descriptive quantitative research methods. Data collection techniques by means of observation and distributing questionnaires to 31 respondents of Bank BJB Syariah Cirebon Branch employees. The data analysis used is classical assumption test, multiple linear regression analysis, coefficient of determination, and hypothesis testing using the help of SPSS version 22.0 software. Based on the results of the study, it shows that the variables of internal audit and internal control partially and simultaneously have a significant effect on fraud prevention at Bank BJB Syariah Cirebon Branch.